Connecting and Collaborating Within and Beyond a Massive Open Online Course. Issue 2 (26th May 2016) - Pytash, Kristine E.; Hicks, Troy; Ferdig, Richard E.
Abstract: In this article, we draw on the experiences of two young adults, Beth and Jamie (pseudonyms), who participated in a connectivist Massive Open Online Course (cMOOC) to explore how adolescents can become active members in a community of learners and the digital literacy practices that support this entry. We argue that Beth and Jamie engaged in digital literacy practices that allowed them to be socially connected, and that they participated and established themselves as equal members in a community of practice. Their experiences has implications for how we engage students in literacy experiences that encourage them to be connected learners in larger communities of practice.